Effect of harvesting time and storage on essential oil and PEME content of Pandanus fascicularis - Noohi Nasim, Jay Krishna Behera, I. Sriram Sandeep, Basudeba Kar, V.V. Ramarao, Ramesh Srivastava, Sanghamitra Nayak, Sujata Mohanty (Journal of Applied Pharmaceutical Science, 2017)
Pandanus fascicularis L. commonly known as kewda is an important aromatic and medicinal plant belonging to the family Pandanaceae. The kewda oil has a characteristic aroma mainly due to the presence of phenyl ethyl methyl ether (PEME). In addition, terpinen-4-ol, α-terpineol and p-cymene also contribute to the fragrance of the oil. Owing to its aroma, kewda oil possesses great demand in flavour and fragrance industry. Due to high volatile nature of PEME, the flower harvesting and storage procedures play an important role in quality and yield of oil. Keeping this in view, the present experiment was carried out where the essential oil was isolated from freshly plucked flowers and cold stored kewda flowers (stored at 4 ºC) at 0 hr, 3 hrs and 6 hrs respectively. The essential oil was then subjected to GC and GC-MS analysis. The results revealed that the PEME percentage decreased in fresh and stored flowers from 0 hr (82%) to 3 hrs (77%, 72%) and 6 hrs (46%, 68%). PEME and terpinen-4-ol content was higher in cold stored flowers than fresh flowers at both the time intervals. Thus, harvesting time and storage of flower play a crucial role in kewda oil yield and quality.
Keywords: Pandanus fascicularis, essential oil, harvesting time, PEME content.